2018
DOI: 10.1007/s00431-018-3211-1
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index at the presentation of premature adrenarche is associated with components of metabolic syndrome at puberty

Abstract: The aim of this study was to analyze the relationship between premature adrenarche (PA) and metabolic syndrome (MeS) parameters at presentation and during puberty. This study comprised 47 girls with PA. Age- and puberty-matched 22 healthy girls without PA were the control group. Patients were evaluated at admission (first evaluation) and later in puberty (second evaluation). Anthropometric measurements, lipid levels, and hormonal parameters were studied and oral glucose tolerance test was performed. Indices fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
19
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 30 publications
3
19
1
Order By: Relevance
“…Hyperinsulinemia is a common finding among prepubertal children with PA [8, 9, 14] and the risk of decreased insulin sensitivity seems to be increased in girls with PA also at adolescence [7, 12]. In a study investigating Turkish girls with PP, decreased insulin sensitivity at pubertal age could be predicted mostly by prepubertal BMI [12]. Our current study findings indicate the risk of abnormalities in glucose metabolism persists to adult age and that the risk is strongly associated with central adiposity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyperinsulinemia is a common finding among prepubertal children with PA [8, 9, 14] and the risk of decreased insulin sensitivity seems to be increased in girls with PA also at adolescence [7, 12]. In a study investigating Turkish girls with PP, decreased insulin sensitivity at pubertal age could be predicted mostly by prepubertal BMI [12]. Our current study findings indicate the risk of abnormalities in glucose metabolism persists to adult age and that the risk is strongly associated with central adiposity.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported also an unfavorable lipid profile [7, 10] or slightly increased blood pressure (BP) in prepubertal girls with PP [4]. A tendency to be overweight and hyperinsulinemic seems to persist at least until early puberty [7, 11, 12], and it has been suggested that PA is a risk factor for the development of later cardiometabolic abnormalities, such as the metabolic syndrome (MetS) [13]. However, the number of studies exploring long-term cardiovascular risk profile and adult outcomes of PA is limited.…”
mentioning
confidence: 99%
“…PP has been associated with obesity, hyperinsulinemia, and hyperandrogenism; however, it is not clear whether the primum movens is overweight or hyperandrogenism. A higher prevalence of overweight among children with PP has been recently documented [47, 50-52], and body weight is thought to be involved in the onset of pubarche [1, 3]. Some studies have shown that overweight girls tend to experience an earlier onset and a more rapid evolution of puberty and pubarche [53-55].…”
Section: Discussionmentioning
confidence: 99%
“…Benign premature adrenarche (BPA) is a clinical diagnosis often associated with elevations of dehydroepiandrosterone (DHEA) and dehydroepiandrosterone sulfate (DHEAS) for chronological age,. 9,10 If phenotypic signs of androgen activity, such as pubic and/or axillary hair, adult-type body odor, oily skin or hair, comedones, or accelerated growth velocity, are detected before the age of 8 in females or 9 in males, premature adrenarche is present. 9 Prior studies have found increased rates of obesity in children with BPA.…”
Section: Introductionmentioning
confidence: 99%